2021
DOI: 10.1016/j.lindif.2021.101972
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement, truancy, and cynicism: A longitudinal study from primary school to upper secondary education

Abstract: Truancy in upper secondary education is a widespread problem, which contributes significantly to school dropout risk. However, the underlying mechanisms of truancy have remained unstudied. This longitudinal study of 1853 Finnish students examined how initial levels and changes in student engagement from primary (Grade 6) to lower secondary school (Grades 7 and 9) predicted truancy in upper secondary education, and whether cynicism (losing interest in school) mediated the relationship between engagement and tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…In the present study, we focus on a different set of potential mediators of gender difference: school enjoyment, school engagement, task value for literacy, and two school burnout symptoms, that is, exhaustion and cynicism. We expect that shortcomings in one or several of these domains may have a negative effect on all parts of schooling, including the development of reading skills or the effort invested in doing one's best in a reading test (e.g., Anmarkrud & Bråten, 2009;Malanchini et al, 2017;Taboada et al, 2009;Virtanen et al, 2021;Wigfield et al, 2012).…”
Section: Gap In Readingmentioning
confidence: 99%
“…In the present study, we focus on a different set of potential mediators of gender difference: school enjoyment, school engagement, task value for literacy, and two school burnout symptoms, that is, exhaustion and cynicism. We expect that shortcomings in one or several of these domains may have a negative effect on all parts of schooling, including the development of reading skills or the effort invested in doing one's best in a reading test (e.g., Anmarkrud & Bråten, 2009;Malanchini et al, 2017;Taboada et al, 2009;Virtanen et al, 2021;Wigfield et al, 2012).…”
Section: Gap In Readingmentioning
confidence: 99%
“…Recently, Liu et al (2017) found cynicism to be inversely related to medical interns' engagement. Similarly, in a study on Finnish students, Virtanen et al (2021) found a negative association between cynicism and engagement. Therefore, it is hypothesized that, H3.…”
Section: Reducing Intern Cynicismmentioning
confidence: 80%
“…Parents give the highest rating to the educational work of the school on the formation of such personality traits in their children as honesty in relationships with people, kindness in relationships with people, fairness in relationships with people, and interest in learning. Studies show that a high level of interest in learning is subsequently associated with less absenteeism and higher academic results [6]. To a lesser extent, parents are satisfied with the extent to which school fosters high life needs, will and tolerance for the views and opinions of other people, and positive life goals in their children.…”
Section: Resultsmentioning
confidence: 99%